Податкове планування як інструмент системи управління підприємством - Перерва, Петро Григорович; Лега, Ольга Василівна; Яловега, Людмила Василівна (Видавничий дім "Гельветика", 2024)
Діяльність економічних агентів пов’язана з необхідністю максимізації фінансових ресурсів, що пере-бувають у їхньому розпорядженні. У цьому контексті податкові розрахунки залишаються проблемним питанням стосовно взаємодії держави та платників податків, оскільки у процесі оподаткування завжди існують суперечливі цілі. Питання податкового планування та податкової оптимізації має важливе стратегічне значення, оскільки дотримання балансу між інтересами держави, юридичних та фізичних осіб забезпечує як достатній рівень податкових надходжень для фінансування суспільних потреб, так і інтереси компаній, які продовжують та розширюють свою господарську діяльність в рамках правового поля. Це пов’язано з тим, що майже всі господарські операції мають податкові наслідки, врахування яких дозволяє підвищити ефективність господарської діяльності та максимізувати прибутки підприємств.
Tax planning as a tool of the enterprise management system
The activity of economic agents is associated with the need to maximise the financial resources at their disposal. In this context, tax calculations remain a problematic issue in terms of interaction between the state and taxpayers, since there are always contradictory objectives in the process of taxation. The issue of tax planning and taxoptimisation is of great strategic importance. This is caused by maintaining a balance between the interests of the state, legal entities and individuals. In addition, such measures ensure both a sufficient level of tax revenues to finance public needs and protect the interests of companies that continue and expand their business activities within the legal framework. However, this is due to the fact that almost all business operations have tax consequences, the accounting of which makes it possible to increase the efficiency of economic activity and maximise the profit of companies. The purpose of the study is to highlight the theoretical and practical foundations of tax planning, which is carried out by a business entity. To achieve the purpose of the article, modern publications of scientists in terms of the problems of tax planning of domestic enterprises have been studied. Also the views of scientists and specialists on the definition of the essence of the category «tax planning» are generalised. It is established that scientists interpret the essence of tax planning in different ways (options for choosing financial and economic activities, approach to the organisation of the enterprise's activities, an element of the tax policy of the enterprise, the system of bodies managing the tax process, rules and requirements governing tax actions, the possibilities of ccounting methods; the process of forming an accounting policy in terms of tax calculations, etc.). But the goal is to reduce the tax burden using legally valid regulations. In other words, modern tax planning can be described as a series of actions carried out by taxpayers within the framework of legislation to optimise taxation in order to reduce tax liabilities and reduce the tax burden on business. Therefore, the article highlights the goals, objectives and functions of tax planning at the stages of functioning of enterprises in the context of creation, operation and termination
Keywords: податкове планування; оптимізація; податкове навантаження; платники податків; законодавство; tax planning; optimisation; tax burden; taxpayers; legislation